PENGARUH FINTECH PAYMENT DAN LITERASI KEUANGAN TERHADAP PERILAKU KONSUMSI MAHASISWA FEBI IAI DARUSSALAM MARTAPURA - Septian Pajrin Mukti; Lola Malihah; Husna Karrimah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2023)
This research aims to determine the partial and simultaneous effects of fintech payment and financial literacy on the consumption behavior of students at the Faculty of Economics and Islamic Business at IAI Darussalam Martapura. Data collection was carried out using a questionnaire with 146 students as the research sample. The data analysis techniques used were descriptive analysis and multiple regression analysis using SPSS 26 for Windows. Based on the research results, it is known that the fintech payment variable (X1) has a partial effect on the student's consumption behavior variable (Y), while the financial literacy variable (X2) does not have a significant effect on the dependent variable. Furthermore, both independent variables, fintech payment (X1) and financial literacy (X2), have a simultaneous effect on consumption behavior (Y).